2001
DOI: 10.1890/1051-0761(2001)011[1194:nppous]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Net Primary Production of U.S. Midwest Croplands From Agricultural Harvest Yield Data

Abstract: We studied crop harvested yield, as recorded in national agricultural statistics, to estimate net primary production (NPP) in agricultural regions where most of the land area is sown with a few, well-studied crops. We estimated the magnitudes and interannual variations in NPP in croplands in the U.S. Midwest using crop area and yield data obtained from the U.S. National Agricultural Statistics Service (NASS). Total NPP, including estimates of the above-and belowground components, was calculated from harvested-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(130 citation statements)
references
References 48 publications
7
118
1
Order By: Relevance
“…Methods have been developed for estimating carbon uptake by agricultural crops Lobell et al 2002;Prince et al 2001). These methods can be used to estimate carbon uptake at the county level within the US.…”
Section: Methods Of Carbon Accountingmentioning
confidence: 99%
“…Methods have been developed for estimating carbon uptake by agricultural crops Lobell et al 2002;Prince et al 2001). These methods can be used to estimate carbon uptake at the county level within the US.…”
Section: Methods Of Carbon Accountingmentioning
confidence: 99%
“…To exclude regions with sparse agriculture, our analysis was confined to counties with at least 10% of the total area planted in corn and soybean (661 counties were analyzed). Following methods outlined in previous agricultural studies (Prince et al, 2001;Reeves et al, 2005), we translated the reported grain productions to annual GPP. The translation takes equations that are analogous to the allometric equations for forest biomass estimation as follows:…”
Section: Regional Datamentioning
confidence: 99%
“…In the case of the unfertilized (NA-series) subplots, crop K removal was intensified by the harvest of corn or oats stover until 1967, estimated at 331 kg K ha − 1 for continuous corn, 310 kg K ha − 1 for the corn-oats rotation, and 256 kg K ha − 1 for the corn-oatshay rotation. To account for K removal in these residues, a harvest index of 0.5 was assumed for both crops [29][30][31][32] , and a K concentration of 13.5 (corn) or 15 (oats) kg Mg − 1 of dry matter 33 .…”
Section: Morrow Plots Potassium Balance Studymentioning
confidence: 99%
“…The importance of non-exchangeable and mineral K for plant uptake is by no means unique to micaceous clays, which are subject to biological weathering in the rhizosphere [91][92][93][94] (see also supplemental references [28] and [31] for the online version of the paper). Sand-and siltsized muscovite and biotite can also be a major source of plant-available K, as demonstrated conclusively by Mengel et al 83 in studies with 14 loess-derived Alfisols.…”
Section: Evaluation Of Soil Potassium Testingmentioning
confidence: 99%